Multimodal Analysis of the Term "Star" in the Qur'an on Agus Mustofa's YouTube Channel - Zainur Rozikin (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
The concept of "star" in the Qur'an presents a complex natural phenomenon expressed through five distinct terms, yet Indonesian translations often conflate these into a single term, "bintang-bintang," which risks misunderstanding. This study addresses this issue by examining Agus Mustofa’s interpretation of these terms on his YouTube channel, focusing on how visual and multimodal elements contribute to his discourse. Previous research has largely overlooked the interplay between religious terminology and digital visual media, creating a gap this study aims to fill. The research problem centers on how Agus Mustofa interprets and conveys the term "star" within the Qur'an using multimodal discourse. Conducted qualitatively with a netnographic approach, the study analyzes digital cultural traces from Agus Mustofa’s videos. Data collection involved reviewing his video content, while multimodal discourse analysis examined language alongside visuals, symbolism, gestures, music, and sound, based on Kress and van Leeuwen’s theory. Findings reveal that Agus Mustofa distinguishes al-kawkab as planet, an-najm as star, al-buruj as star clusters and galaxies, al-misbah as meteor showers, and al-khunnas as black holes or neutron stars. This research recommends further exploration of religious multimedia interpretations and encourages expanding multimodal frameworks in digital religious studies.